Investigating the Rebound Effects from Improved Efficiency of Gasoil and Gasoline in Iran by Focusing on Transportation Sector: Computable General Equilibrium Approach - Musa Khoshkalam Khosroshahi (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2014)
Since the consumption of gasoil and gasoline in the Iranian economy, especially in the transportation sector is high, It is essential to thought serious solutions to improve the efficiency of these two petroleum products in various sectors. Improve the efficiency of gasoline and gasoil coupled with a problem called rebound effect (RE) Where the initial reduction in gasoline and gasoil consumption resulting in improved performance, partially neutralized. It is natural that neglecting the effect of the consumption of gasoline and gasoil would undermine the policy optimization. The purpose of this paper is to measuring the RE and changes in the transport sub-sector activity following a 10-percent improvement in efficiency of gasoline and gasoil. CGE model based on SAM1385 have been used to achieve the purposes of the paper. The results show that following a 10-percent improvement in efficiency of gasoline and gasoil, the maximum amount of RE for gasoline is in road transport sector (27.45 percent) and maximum amount of RE for gasoil is in road transport sector (25.21 percent). The average total RE of gasoline is equal 12.95% and for gasoil is equal 13.79%. It is noteworthy that following a 10-percent improvement in efficiency of gasoline and gasoil, rail transport sector has the greatest increase in activity level (13.4 percent).